Cognitive computing in technology-enhanced learning - Lytras, Miltiadis D. 1973-; Aljohani, Naif 1983-; Daniela, Linda 1967-; Visvizi, Anna 1976- (IGI Global, 2019)
"This book investigates the new era of technology-enhanced learning from a learning analytics and innovation perspective. It also examines state-of-the art approaches of advanced data mining systems in e-leaning, such as MOOCs and other innovative technologies"--